Microsurgical Hepatic Artery Reconstruction Using Ikuta A-II Double Clamp. Issue 5 (May 2017) - Okochi, Masayuki; Okochi, Hiromi; Sakaba, Takao; Momiyama, Masanori; Ueda, Kazuki
Abstract : Summary: We performed hepatic artery (HA) reconstruction on 24 patients between January 2010 and October 2016. Six of 24 patients used an Ikuta type A-II vascular clamp (A-II group). The mean age was 38.0 years (range, 1–61 years). There was no blood leakage at the anastomosed site in any of the patients. No patients required an additional vascular clamp, and none developed HA thrombosis. Eighteen of 24 patients used a conventional vascular clamp. The mean age was 36.1 years (range, 1–65 years; conventional group). Sixteen of 18 patients required an additional vascular clamp due to blood leakage from the HA. There was no significant difference between the 2 groups in mean age or diameter of the recipient HA. However, there was a significant difference in the proportion of patients who required an additional vascular clamp (n < 0.001). The Ikuta type A-II clamp is an effective vascular clamp for reconstruction of the HA in living donor liver transplantation. Abstract : Supplemental Digital Content is available in the text.